Conciliatory Committee and Hakam (arbitrator) under the Islamic family law in Malaysia - Abdul Hak, Nora (LexisNexis Malaysia Sdn Bhd, 2008)
In Malaysia, the administration of Islamic family law is under the separate jurisdiction of different states where each state has its own enactment over matters relating to family law governing Muslims. In this article, the discussion focuses upon the provisions on dispute resolutions under the Islamic Family Law (Federal Territories) Act 1984, whici is the model Act followed by other states in Malaysia. The article traces in general the historical background of the IFLA 1984. The main focus of the article is on the provisions concerning the dispute resolution, which is provided for under ss 47(5) to (17) and 48 of the IFLA 1984. These relevant provisions are discussed against the background of the principles and rules of tahkim (arbitration) as deliberated in the sources of syariah.